A análise retrospectiva da exposição de motivos da lei maria da penha: um diálogo sobre a eficácia das intenções legislativas diante da necessidade de proteção da dignidade da mulher - Silveira, Priscila Cristina Silva da (2022)
This work is based on the study of the Explanation Of Reasons that served as a substitute for the promulgation of Law 11.340, of August 7, 2006, popularly known as Maria da Penha Law. The law in question aims to curb violence against women and penalize their ordinator more harshly. We will succinctly check the reasons for the creation of this Law. It is known that the subject dealt with is a social problem and causes repercussions not only to the victim, but also to those who are part of their conviviality, causing damage that is difficult to repair and sometimes, with consequences so robust that they perpetuate throughout their lives. The Maria da Penha Law finds its foundation in Article 226, § 8, where "The State shall ensure assistance to the family in the person of each of those who integrate it, creating mechanisms to curb violence within the framework of its relations". Thus, it is intended, to explain broadly, the changes over time and substantial adaptations is, in order to ensure the effectiveness of the applicability of the Maria da Penha Law. The relevant points will be presented together with the advances and possible stagnation brought by the Law and what is intended with the present work, is to demonstrate that domestic violence against women occurs daily and that it is a social problem that needs to be addressed, because it causes irreparable harm to many women all over the world, generating health problems for the rest of life. Violence against women is still a reality and there is not only one cause that can characterize it, but multiple causes. This thesis sought to problematize the use of the Maria da Penha Law as a legal resource for coping with domestic violence in the face of legislative intention due to the need to protect women's dignity